PENGEMBANGAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA BAGI MAHASISWA PEDIDIKAN GURU SEKOLAH DASAR - Wahyudi, Wahyudi (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2016)
Model Development Realistic Mathematics Education (RME) inImproving Student Learning Mathematics for Elementary School Teacher.The purpose of this study are to describe: (1) Realistic Mathematics Education (RME) in improving Mathematics learning to the students in Department of Primary Schools Teacher Education, Faculty of Teacher Training and Education, Sebelas Maret University (PGSD FKIP UNS) campus of Kebumen, (2) reconstruction the curriculum of Mathematics Educationsubject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME), and (3) the construction of teaching material books of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME). The research method is Classroom Action Research (CAR) with cyclical model, involving four steps simultaneously as follows: (1) planning, (2) action, (3) observation, and (4) reflection. Subject of this research was all students at the fourth semester in Department of PGSD FKIP UNS Campus of Kebumen in the academic year 2014/2015, totaling 71 students. Techniques of collecting data used by the researcher were observation, interview, and test. Validity of data used in this research was the techniques of triangulation of source, method, and theory. Techniques of analyzing data was descriptivequalitative data analysis, including data reduction, data display, and drawing conclusion or verification. The results of this research are: (1) the Realistic Mathematics Education (RME) model can improve Mathematics learning to the students in the Department of PGSD FKIP UNS campus of Kebumen, (2) reconstruction the curriculum of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen, and (3) the teaching material books of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME).Â Pengembangan Model Realistic Mathematics Education (RME)dalam Peningkatan Pembelajaran Matematika bagi Mahasiswa PendidikanGuru Sekolah Dasar. Penelitian ini bertujuan untuk mendeskripsikan: (1)Model Realistic Mathematics Education (RME) dalam PeningkatanPembelajaran Matematika bagi Mahasiswa Prodi PGSD FKIP UNS KampusKebumen, (2) Rekonstruksi kurikulum Mata Kuliah Pendidikan Matematikapada Program studi PGSD FKIP UNS Kampus Kebumen berbasis RealisticMathematics Education (RME), (3) Penyusunan Buku Ajar Mata KuliahPendidikan Matematika pada Program Studi PGSD FKIP UNS KampusKebumen berbasis Realistic Mathematics Education (RME). Penelitian ini menggunakan jenis Penelitian Tindakan Kelas (PTK) model Siklus yangmelibatkan 4 langkah dalam setiap siklusnya, yaitu (1) perencanaan, (2)pelaksanaan, (3) observasi, dan (4) refleksi. Penelitian ini melibatkan subjek penelitian sebanyak 71 mahasiswa Semester IV Prodi PGSD FKIP UNS Kampus Kebumen Tahun Akademik 2014/2015. Teknik pengumpulan data yang digunakan adalah: (a) observasi, (b) wawancara, dan (c) tes. Validitas data yang digunakan pada penelitian ini adalah dengan teknik Triangulasi sumber, metode, dan teori. Adapun Teknik analisis data yang digunakan adalah deskriptif kualitatif yang terdiri dari tiga alur secara berkelanjutan yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini adalah: (1) Model Realistic Mathematics Education (RME) dalam Peningkatan Pembelajaran Matematika bagi Mahasiswa Prodi PGSD FKIP UNS Kampus Kebumen, (2) Rekonstruksi kurikulum Mata Kuliah Pendidikan Matematika pada Program studi PGSD FKIP UNS Kampus Kebumen berbasis Realistic Mathematics Education (RME), (3) Buku Ajar Mata Kuliah Pendidikan Matematika pada Program studi PGSD FKIP UNS Kampus Kebumen berbasis Realistic Mathematics Education (RME).